Antiproliferative effects of fresh water crab hemolymph and meat extract on breast cancer cell line - Rezakhani, Leila; Alizadeh, Morteza; Sharifi, Esmaeel; Soleimannejad, Mostafa; Alizadeh, Akram (Journal of Shahrekord University of Medical Sciences, 2021)
Background and aims: Despite the advances in drugs, side effects of chemotherapy drugs continue to exist. Therefore, more attention has been paid to the compounds derived from medicinal herbs and aquatic organisms. This study aimed to investigate the effect of freshwater crab hemolymph and meat extract on breast cancer (BC) cell line (4T1). Methods: After isolation of freshwater crab hemolymph and meat extract, protein concentration and total antioxidant capacity were analyzed by bicinchoninic acid (BCA) and cupric reducing antioxidant capacity (CUPRAC) methods. The 4T1 cells and bone marrow mesenchymal stem cells (BMSCs) were treated with crab hemolymph (1, 2, 10 mg/mL) and meat extract (0.1, 0.2 and 1 mg/mL), and cell survival was analyzed using 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay (MTT) at 48 and 72 hours. Nitric oxide (NO) secretion was measured by Griess method. Data were analyzed using one-way analysis of variance (ANOVA). Results: Protein concentration of 23.25 mg/mL was shown in crab hemolymph, and 2.3 mg/mL in meat extract. Total antioxidant capacity was reported as 1.036 µM/mL and 1.104 µM/mL in crab hemolymph and meat extract, respectively. Cell survival in the 4T1 cells was decreased in a dose- and time-dependent manner (P≤0.001). NO secretion of 4T1 cells was decreased after treatment with different concentrations of crab hemolymph and meat extract at 48 and 72 hours. Cellular growth was observed in BMSCs after treatment with different concentrations of crab hemolymph and meat extract at 48 and 72 hours. Conclusion: Since crab hemolymph and meat extract have protein and antioxidant activities, they can have anti-cancer effects on 4T1 cells.